NEEDS ANALYSIS OF PROJECT BASED LEARNING AND PROBLEM BASED LEARNING METHODS TO IMPROVE HIGHER ORDER THINKING SKILLS - Sela Maulina; Nuryadi Nuryadi; Nanang Sahid Wahyudi (Sean Institute, 2023)
Higher Order Thinking Skill is one of the abilities that students must have in the Merdeka Belajar curriculum. This requirement is a form of effort made to improve the qulity of education in Indonesia. Given that the results of the PISA conducted in 2018, Indonesia was ranked 74 out of 76 countries and received an average score, especially mathematics, namely 379. For this reason, higher order thinking skill especially mathematics, must be improved so that the quality of education in Indonesia can increase. The purpose of this research is to analyze the need for project based learning and problem based learning methods to improve higher order thinking skill. The research subject were the 8 grade students of SMP Negeri 8 Yogyakarta. The methode used is descriptive qualitative research method. Data collection techniques using interview, observation, and questionnaires. This research found that it is necessary to apply project based learning and problem based learning methods to help students improve their higher order thinking skill